Redressing The Online Transaction Fraud Victim Treatment And Interest Fulfillment In Criminal Justice System - Samudra, Anton Hendrik (UI Scholars Hub, 2019)
This article gives idea on how to redress online transaction fraud victim in criminal justice system. The method applied is by looking scholars’ studies, statutes, observation of victimization process and interviewing law enforcement and victim. In several occasions, investigators turned to blame the victim when they report the crime. For several unsolved cases, the victim asked to revoke their report. This caused by investigator’s view that victim recklessness and failure to think what is deservedly suppose is the main cause of the crime. Treatment and interest fulfillment of online transaction fraud victim in criminal justice system should be redressed, such as the accommodation of material loss recovery, and regarding the victim’s interest during criminal justice process.